Critical Thinking in Solving Two-Variable Equation Word Problems: A Case Study by Gender Identity - Nuriati, Esti; Siswono , Tatag Yuli Eko; Harini, Novita Vindri (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
Junior high school students' critical thinking in solving systems of linear equations often exhibits weaknesses, particularly in assessment and reasoning stages, which may hinder deep algebraic understanding. This study analyses students' critical thinking abilities according to Facione's indicators and explores how gender identity, measured through the Bem Sex Role Inventory, influences these patterns. This research contributes novel insights by systematically examining the intersection of critical thinking development and gender identity in algebraic problem-solving contexts. A descriptive case study methodology employed purposive sampling of four ninth-grade students at a junior high school in East Java, classified as masculine male, feminine male, masculine female, and feminine female based on BSRI scores. Data were collected through written tests, semi-structured interviews, observations, and documentation, then triangulated in analysis. Findings revealed distinct patterns: masculine males excelled in analysis and reasoning but lacked assessment skills; feminine males showed strong comprehension and articulation yet weak reasoning; masculine females demonstrated proficiency in analysis and assessment with less systematic explanations; and feminine females exhibited strong comprehension and articulation but limited analytical abilities. This study provides the first comprehensive framework linking gender identity profiles with critical thinking patterns in mathematical problem-solving, offering evidence-based guidance for developing inclusive instructional strategies in junior high mathematics.